2010
DOI: 10.1007/s11745-010-3496-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stability of Marine Phospholipids in the Liposomal Form and Their Applications

Abstract: Marine phospholipids (MPL) have attracted a great deal of attention recently as they are considered to have a better bioavailability, a better resistance towards oxidation and a higher content of eicosapentaenoic (EPA) and docosahexaenoic acids (DHA) than oily triglycerides (fish oil) from the same source. Due to their tight intermolecular packing conformation at the sn-2 position and their synergism with α-tocopherol present in MPL extracts, they can form stable liposomes which are attractive ingredients for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(38 citation statements)
references
References 158 publications
0
36
0
2
Order By: Relevance
“…Even though this study was not designed as to compare the effects of fish oil to that of krill oil, other studies allows hypothesizing that the molecular form of the supplemented n-3 PUFA is of importance to their various effects [10]. It was recently demonstrated that the incorporation of EPA and DHA into myocardial phospholipids was higher when delivered in the form of krill oil/n-3 phospholipids, compared to n-3 bound in the form of triglycerides (fish oil) [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though this study was not designed as to compare the effects of fish oil to that of krill oil, other studies allows hypothesizing that the molecular form of the supplemented n-3 PUFA is of importance to their various effects [10]. It was recently demonstrated that the incorporation of EPA and DHA into myocardial phospholipids was higher when delivered in the form of krill oil/n-3 phospholipids, compared to n-3 bound in the form of triglycerides (fish oil) [27].…”
Section: Discussionmentioning
confidence: 99%
“…This molecular makeup is different from traditional fish oils, where the n-3 PUFA are mainly bound to triglycerides or ethyl esters [9]. This difference may be important as the molecular form of n-3 PUFA has been suggested relevant for their biological effects [10]. Furthermore, phospholipids themselves have been shown to have beneficial effects on lipid metabolism [11].…”
Section: Introductionmentioning
confidence: 99%
“…Además, la estabilidad a la oxidación de los AGPICL, a la cual son muy susceptibles, es mayor cuando estos ácidos grasos se encuentran en la estructura de los fosfolípidos (27), aspecto que es de importancia desde el punto de vista de la estabilidad de las estructuras celulares y también de aquellos productos que sean adicionados de este tipo de fosfolípidos.…”
Section: Funciones Y Propiedades De Los Fosfolípidosunclassified
“…Son más estables al desarrollo de procesos oxidativos que los triglicéridos con composición equivalente de AGPICL (27). A nivel digestivo, los ácidos grasos tienen mayor biodisponibilidad cuando provienen de fosfolípidos que los aportados por la hidrólisis de los triglicéridos (28,29).…”
Section: Funciones Y Propiedades De Los Fosfolípidosunclassified
“…It exhibits broad bioactivity including inducing apoptosis of scar cells [1] and anti-inflammatory [2] and anticancer [3, 4] properties, which have been used in the traditional Chinese medicine for treatment of hypertrophic scar, inflammation, cancer, and other diseases without obvious toxicity or side effect in clinic. Several preparions, hydrogel [5], lotion [6], injection [7], and liposome [8], for example, have been reported in the literature. We are further interested in the form of liquid crystalline nanoparticles (cubosome), for cubosome consists of a curved bicontinuous lipid bilayer extending in three dimensions and separating two congruent networks of water channels [911], which can enclose hydrophilic, amphiphilic, and hydrophobic substances ranging from low-molecular-weight drugs to proteins, peptides, amino acids, and nucleic acids [12].…”
Section: Introductionmentioning
confidence: 99%